Analisis Pengaruh Kualitas Layanan, Kualitas Produk, Dan Kepercayaan Pelanggan Terhadap Keputusan Pembelian (Studi Empiris Menggunakan Platform E-Commerce) - Simbolon, Josua; Fitriyani, Iis (Shofanah Media Berkah, 2023)
This research aims to analyse the influence of service quality, product quality, and customer trust on purchasing decisions. This research uses qualitative analysis methods, classical assumption tests, regression analysis, and hypothesis testing. The sample in this research is consumers who buy products or services from e-commerce or online from the five most frequently used e-commerce platforms. The research results show that service quality and customer trust have a positive and significant effect on purchasing decisions, while product quality has no effect on purchasing decisions. Therefore, companies need to improve service quality and customer trust to maintain purchasing decisions and continue to increase.